2003
DOI: 10.1007/s00442-003-1389-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of net ecosystem gas exchange to a simulated precipitation pulse in a semi-arid grassland: the role of native versus non-native grasses and soil texture

Abstract: Physiological activity and structural dynamics in arid and semi-arid ecosystems are driven by discrete inputs or "pulses" of growing season precipitation. Here we describe the short-term dynamics of ecosystem physiology in experimental stands of native (Heteropogon contortus) and invasive (Eragrostis lehmanniana) grasses to an irrigation pulse across two geomorphic surfaces with distinctly different soils: a Pleistocene-aged surface with high clay content in a strongly horizonated soil, and a Holocene-aged sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
238
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(252 citation statements)
references
References 43 publications
12
238
0
2
Order By: Relevance
“…Likewise, Fierer and Schimel (2002) found that frequent exposure to drying-rewetting events decreased the amount of CO 2 released upon rewetting. Respiration occurred throughout this study, even when the soil was very dry, most likely due to the continued activity of perennial plants (Huxman et al, 2004b). Reflecting the plant activity alone, T and GEP had similar responses in time, though peaks in GEP appeared to precede T by a day or two.…”
Section: Relationships Between Components Of Et and Neementioning
confidence: 78%
See 2 more Smart Citations
“…Likewise, Fierer and Schimel (2002) found that frequent exposure to drying-rewetting events decreased the amount of CO 2 released upon rewetting. Respiration occurred throughout this study, even when the soil was very dry, most likely due to the continued activity of perennial plants (Huxman et al, 2004b). Reflecting the plant activity alone, T and GEP had similar responses in time, though peaks in GEP appeared to precede T by a day or two.…”
Section: Relationships Between Components Of Et and Neementioning
confidence: 78%
“…Consequently, we caution that the computed R and GEP presented below likely contain considerable error. This uncertainty is not unexpected owing to the myriad of processes, not accounted for in the standard respiration models, that may influence total CO 2 efflux in semiarid areas and which include (1) the physical displacement of CO 2 following rainfall event, (2) the biological activity of both aboveground and belowground autotrophic biomass, (3) the microbial activity in close association with roots and the microbial (Huxman et al, 2004b;Fisher and Whitford, 1995;Emmerich, 2003).…”
Section: Transpiration and Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent work has examined the relationship between exotic grasses and rainfall pulses (Huxman et al 2004;Clarke et al 2005). But very little work has directly examined how invasive species might be influencing the water cycle in these environments.…”
Section: What Are the Ecohydrological Consequences Of Invasion By Exomentioning
confidence: 99%
“…Similarly, evapotranspiration (ET) represents the sum of stomata-mediated transpiration and evaporation from soil and canopy surfaces and is an important link in the movement of water between ecosystems and the atmosphere. Chamber-based measurements of NEE and ET have been used to demonstrate the impacts of invasive plants on above-and below-ground carbon cycling and ecosystem water balance in semi-arid grasslands of southern Arizona (Huxman et al 2004;Potts et al 2006a) and in the Great Basin (Prater et al 2006).…”
Section: Introductionmentioning
confidence: 99%